Dermatological Diseases of the Nose and Ears An Illustrated Guide - Baykal, Can; Yazganoglu, K. Didem (Springer Berlin Heidelberg : Imprint: Springer, 2010)
"Dermatological Diseases of the Nose and Ears" gives comprehensive information about the lesions of these regions. It contains high quality original clinical pictures, which make the diagnosis easier in this important aspect of clinical dermatological practice. All diseases involving the nose and ears are discussed separately with a clinical differential diagnostic approach. As a result approximately 600 different diseases are addressed in the book. In clinical practice, physicians may observe lesions of the nose or ear only. After identifying the elementary lesion, the clinician can more easily uncover the diagnosis of a local or disseminated or systemic disease with the help of this book. Furthermore, this color illustrated book guides the reader to the diagnosis of the prevalent skin tumors frequently involving these localizations, addressing an important health care problem.